FIRST RECORD OF Dolops striata (BRANCHIURA: ARGULIDAE) ON Arapaima gigas FROM A FISH FARM IN STATE OF PARÁ, BRAZIL - PEREIRA, Jeffson Nobre (2017)
Branchiurans are parasites from the buccal cavity, gills, skin, and fins of various fish species. The Neotropical region has one of the highest diversity of branchiurans. On Arapaima gigas, only four species of branchiurans have been reported. The present study improves the knowledge on host and geographical range of Dolops striata. Fish were collected from a fish farm in the State of Pará, Brazil. All A. gigas were parasitized by Dolops striata, which were collected from the fins and body surface. This is the first record of D. striata in A. gigas. The high prevalence detected warns the possibility of an increase in the number of D. striata infesting A. gigas, which may cause some problems for fish-farmers.